Analisis Faktor Produksi dan Kelayakan Usaha Perikanan Purse Seine di Kecamatan Salahutu Kabupaten Maluku Tengah - Johannes, Stylia; Wisudo, Sugeng Hari; Nurani, Tri Wiji (Universitas Brawijaya, Indonesia, 2015)
The principles of biology and technology resources play an important role indeveloping purse seine fisheries, however in the end the success and sustainability anddurability of these efforts also depend on economic principles. Associated with it, there is astudy that has been conducted in order to identify the factors of production of purse seinefishery unit in Subdistrict Salahutu, Central Maluku Regency that affect the productivity aswell as analyzing the financial aspects. The result shows that the production within a yearranged from 113.68 to 243.63 tons with the mean was 173.75 tons. Amounting 98% of theproduction of purse seine catches are influenced by the factors of production such as shipsize, large nets, the number of crew and the amount of fuel. Purse seine fisheries providebenefits ranging from Rp. 412,000,000.- to Rp. 902,234,000.- with the mean was Rp. 736,914,222.-, revenue-cost ratio ranged from 1.9 to 5.4 with the mean was 3.3. The time required by thepurse seine fishery effort to return the invested funds have ranged from 0.5 to 1.1 years withthe mean was 0.6 years. The ability of capital in the Purse Seine Fishery to produce netbenefits ranged from 90.9 to 199.1% with the mean was 162.6%. Purse seine fishery businessis a decent effort to be developed because NPV value > 0, IRR> discount rate and Net B / C >1.